KORUPSI DAN AKUNTANSI FORENSIK - RIKA LIDYAH RIKA (I-Finance Journal, 2016)
Forensic accounting is implementing of accounting discipline in means widely, include auditing to laws problem for inside or outside completion law at laws court, both public sector and private (Tuanakotta, 2010). This References explained that forensic accounting is accurate accounting for law purpose or time-tested accounting in court process or yudicial review process or administrative review. Forensic accounting is a special practice which is describe the involvement from actual dispute or anticipated litigation (Crumbley, 2005). Fraud is criminal cheater that means to give a financial benefit to cheater. This criminals means every serious fault activities due scheme. From this activity he has a benefit and he make the victim loss financelly. Forensic accountant proffession prospect is to involved to settle law cases in Indonesia. Law cases in Indonesia especially related to fraud should have involved forensic accountant to solved, because forensic accountant can help the expert and law enforcer to collect evidence and physical evidence to determine the potential of loss because of fraud. Beside that, forensic accountant prospect more potential because people who work in financial institution have to understand about this forensic accounting. So, it has to detection earlier in other to overcome the difficulties.Key word : Forensic accounting, Fraud, Corruption